2023
DOI: 10.3389/fbinf.2023.1197310
|View full text |Cite
|
Sign up to set email alerts
|

A guide for developing comprehensive systems biology maps of disease mechanisms: planning, construction and maintenance

Abstract: As a conceptual model of disease mechanisms, a disease map integrates available knowledge and is applied for data interpretation, predictions and hypothesis generation. It is possible to model disease mechanisms on different levels of granularity and adjust the approach to the goals of a particular project. This rich environment together with requirements for high-quality network reconstruction makes it challenging for new curators and groups to be quickly introduced to the development methods. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Disease maps are human- and computer-readable repositories containing manually curated interactions following the SBML format, organized into diagrams according to the SBGN notation. The process of map development ( 39 ) involves intensive biocuration work over a selected body of literature. Importantly, interactions of disease maps reference the source literature.…”
Section: Resultsmentioning
confidence: 99%
“…Disease maps are human- and computer-readable repositories containing manually curated interactions following the SBML format, organized into diagrams according to the SBGN notation. The process of map development ( 39 ) involves intensive biocuration work over a selected body of literature. Importantly, interactions of disease maps reference the source literature.…”
Section: Resultsmentioning
confidence: 99%
“…The SYSCID map was constructed by following most of the recommendations in the recently published guidelines for disease maps construction (18). At first, we manually curated reviews and original peer-reviewed research papers suggested by domain experts from the SYSCID consortium.…”
Section: Capturing Ibd- Ra-and Sle-related Causal Interactions From L...mentioning
confidence: 99%